Perceived and expected competencies of government primary health care pharmacists in the Philippines a qualitative study - Dizon III, Ruben C.; Decena, Crystel Sheynne T.; Dela Cruz, Daniella Marie L.; Ngo, Frances Lois U. (Manila Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2025)
Government Primary Health Care (PHC) pharmacists play an important role in service delivery in government primary care facilities. Although national competency standards for pharmacists are outlined in the Philippine Practice Standards for Pharmacists (PhilPSP, 1st Ed.), there is currently a lack of research examining how these competencies align with actual practices in government PHC settings. This study aimed to identify and describe the expected and perceived competencies of government primary health care (PHC) pharmacists as defined by key stakeholders. It further aimed to determine the alignments and gaps between these sets of competencies, compare them with the PhilPSP, 1st Ed., and synthesize a comprehensive competency framework reflecting the actual roles and responsibilities of government PHC pharmacists.

A qualitative descriptive study design was employed. Focus Group Discussions (FGDs) with government PHC pharmacists identified perceived competencies, while Key Informant Interviews (KIIs) with Department of Health and local health officials determined expected competencies. Transcripts were thematically analyzed using NVivo. Perceived and expected competencies were compared and synthesized; the synthesized competencies underwent validation and refinement through an electronic Delphi (e-Delphi) method involving a panel of experts.

The study identified ten core competency standards of government PHC pharmacists. Key gaps were found between expected and perceived competencies, particularly in surveillance, health information management, and service delivery. Comparison with PhilPSP showed overlapping core domains yet indicated the need for additional competencies tailored to government PHC settings.

Findings support the development of separate competency standards tailored to the government PHC setting. These results provide evidence to inform the DOH, PPhA, and CHED in updating training programs, practice standards, and policies, thereby contributing to workforce development and supporting the national implementation of Universal Health Care.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, July 2025
Keywords: Pharmacists -- Competency and performance -- Public sector -- Philippines; Primary health care -- Human resources -- Qualitative studies -- Philippines